BIMBINGAN BAGI ANAK CERDAS DAN ANAK BERBAKAT DI SD ISLAM COKRO AMINOTO 1 KALABAHI - Juliana Albertina Mayopu; Jesenia Loriance Alelang, Imanuel Musa Laukamang, Lala Enggadina Moilegi, Yessy Mata, Petrus Mau Tel (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Child education requires an adaptive approach tailored to the needs and potential of each child. This article discusses the educational strategies for gifted and talented children implemented by a teacher named Mr. Alwi at Cokroaminoto I Islamic Elementary School. The main focus is on differentiating approaches to gifted and talented children, as well as effective collaboration between teachers and parents in guiding children's development. Strategies for handling active children who are often considered "naughty" are also an important discussion, using a humanistic and flexible approach. This study is strengthened by educational theories from Renzulli, Gagné, Bronfenbrenner, Carl Rogers, Howard Gardner, and Thomas Lickona. The results show that inclusive and collaborative strategies can create a more meaningful learning process and encourage the optimal growth of children's potential.